Um burel a plenos pulmões: atuação de Frei Pedro Sinzig na educação franciscana e imprensa católica (1900-1920) - Amâncio, Talita Deniz (2014)
This is a historical research that aimed to research aspects of the trajectory of Pedro Sinzig (1876-1952), Franciscan friar, born in Austria and naturalized Brazilian. He was connected to the Catholic press and directly responsible for the process of modernizing the Vozes Publisher, created by the Franciscans in 1897, at the, Typography Free School St Joseph in Petrópolis, a town of RJ. The chronological approach that directed the research was the period between 1900 and 1920, because it was the moment of greatest intellectual productivity of Sinzig and because it coincides with a series of events in the political and social field of the just proclaimed Republic. The study was based on analysis of books and articles published in newspapers of the time, using the analysis of textual configuration. To do so, we analyzed the periodical Cruzeiro do Sul (1902-1905), produced by Franciscan friars, and O Imparcial, published by members of Santa Catarina's Freemasonry. Both newspapers circulated in the early years of the twentieth century, in the city of Lages, Santa Catarina, and belong to the Santa Catarina's Public Library (BPSC), in Florianopolis. In addition to these materials, an autobiography, which is in the "Coleção Frei Pedro Sinzig", under custody of the Center for Documentation and Research Support in the History of Education (CDAPH), Universidade São Francisco (USF), was also used. Based on the results we can say that the experience of the Sinzig in Franciscan education was brief, but in the field of Catholic Press production was significant, such as discussions with Masons in defense of "good press" and of Catholic education